Pelatihan Manajemen Keuangan dalam Pengembangan Usaha Kecil Menengah - Tola, Damianus; Banda, Yosef Moan; Adrianus, Jou Sewa (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The problem found is that the limited ability of small business actors to manage their business finances has resulted in a poor financial managemeny system that does not yet use the accounting bookkeeping model in financial management. This service aims to help small business actors with defficukties in managing their finances. This Community service uses a participatory action based method which is carried out in Bopoma Village, west Golewa District Ngada Regency. The results of activities can provide serious understanding to small and medium business actors about better financial management. This activity process can increase the knowledge of business actors. The conclusions that can be drawn in this training have a positive effect on small business actor to get to know financial cash flow in depth, create simple financial accounting books, hel ensure that business ventures have sufficient funds to meet financial obligations, overcome financial challenges and take advantage of business growth opportunities, in creating a comprehensive budget.